النظام الإقليمي الخليجي: مسارات التفاعل ومستقبل الإقليم - هجوجي، عبدالمجيد (حليمة عبدالرمي, 2024)
تكمن أهمية الدراسة في رصد التفاعلات البينية التي طرأت داخل النظام الإقليمي الخليجي خلال العقد الأخير، وضبط مسارات العلاقات الخليجية منذ 2014 تاريخ سحب بعض دول منظمة مجلس التعاون الخليجي لسفرائها في سابقة هي الأولى من نوعها من دولة قطر العضو بهذا التكتل، وحتى تطبيع العلاقات السعودية الإيرانية برعاية صينية العام الماضي. وبين الحدثين جرت أمور وأحداث طبعت مسار التفاعلات داخل النظام الإقليمي، حيث كانت تتأزم وتتعقد فتكاد تصل حد المواجهة المسلحة ثم تهدأ وتعود إلى حالة الاستقرار. فسمة العلاقات الخليجية الخليجية خلال العقد المستهدف بالدراسة هو التأرجح بين الصراع والتنافس والتعاون والتكامل بين عدة محاور بالإقليم وبين دول المركز ودول الأطراف، وهي مسارات لعبت فيها دول إقليمية وقوى دولية من خارج الإقليم أدوارا متعددة. بناء عليه، تطرح إشكالية تحديد مسارات التفاعلات داخل الإقليم من جهة ومن جهة أخرى الكشف عن مآلاتها وانعكاساتها على مستقبل الإقليم كنظام فرعي متفرع عن النظام الدولي. The importance of the study lies in monitoring the internal interactions that occurred within the Gulf regional system during the last decade and controlling the paths of Gulf-Gulf relations since 2014, the date when some Gulf Cooperation Council countries withdrew their ambassadors in a precedent that is the first of its kind from the State of Qatar, a member of this bloc, and until the normalization of Saudi-Iranian relations under the auspices of China last year, and between the two events, matters and events took place that marked the course of interactions within the regional system, as they became more complex and complicated, almost reaching the point of armed confrontation, then calming down and returning to a state of stability. The characteristic of Gulf-Gulf relations during the decade targeted by the study is the oscillation between conflict, competition, cooperation, and integration between several axes in the region and between Center countries and periphery countries are paths in which regional countries and international powers from outside the region played multiple roles. Accordingly, the problem of determining the paths of interactions within the region arises on the one hand, and on the other hand, revealing their outcomes and repercussions on the future of the region as a sub-system branching off from the international system.
Keywords: العلاقات الخليجية -- الصراعات الدولية -- النظم السياسية -- المنظمات الإقليمية